The Impact of Globalization on the Business (Global Journal of Human-Social Science, 2015)
The modern liberal, capitalistic and economic actions become a conglomerate of factors and reasons, analysis, information, mediums, skills and predispositions influencing on the business. The participation on the world's global markets, the internationalization and the transfer of the business activities on all geographic meridians, encountering different and often uncertain environments is a constant business story of the international economic activity for at least three centuries ago. The global economic interaction is as old as it is old the society in its more or less organized form. From the industrial revolution until today, there is ongoing irreversible global economic integration. The reasons are simple, business and profits do not recognize borders, national and cultural unsurpassed characteristics, where more or less a mutual benefit of certain cooperation is recognized, a business connection is immediately established. Making an decision for investment on a foreign location is a process of extensive analysis, thoroughly and profound long-term thinking and scanning of the institutional and legal frameworks that should provide in advance, and to some extent, guaranteed predictability, in terms of responsiveness to a certain dilemmas, how much to be invested, where to direct the capital, what will be the economic benefit and the ability to anticipate, in advance, the given risks.
Keywords: internationalization; global markets; economic integration